Kecemasan remaja pada masa pandemi Covid -19 - Linda Fitria; Ifdil Ifdil (Indonesian Institute for Counseling, Education and Therapy (IICET), 2020)
This study aims to describe the level of anxiety experienced by adolescents during the covid-19 pandemic. This research uses descriptive quantitative research methods. The population in this study were adolescents aged 12 to 19 years, with a sample of 139 people. The instrument used was a questionnaire about anxiety. Data analysis uses descriptive analysis. Based on the analysis of research data, teenage anxiety during the covid-19 pandemic was in the high category at 54%.